Baicalein alleviates non-alcoholic fatty liver disease in mice by ameliorating intestinal barrier dysfunction. Issue 4 (8th February 2023) - Guo, Chunyu; Li, Qingjun; Chen, Rihong; Fan, Wenhui; Zhang, Xin; Zhang, Yuqian; Guo, Lanping; Wang, Xiao; Qu, Xinyan; Dong, Hongjing
Abstract : Baicalein ameliorated MCD diet-induced inflammation and hepatic lipid accumulation and protected intestinal integrity. Abstract : Non-alcoholic fatty liver disease (NAFLD) is the main cause of chronic liver disease, and its pathological development is closely related to the gut–liver axis. The intestinal barrier, an important component of the gut–liver axis, can prevent gut microbes and endotoxins from entering the liver. Intestinal barrier function is impaired in patients with NAFLD. Baicalein, which is the main flavonoid in Scutellariae Radix, can improve NAFLD. However, whether baicalein alleviates NAFLD by ameliorating intestinal barrier dysfunction remains unclear. In this study, a methionine–choline deficient (MCD) diet-induced NAFLD mouse model is used. The effects of baicalein on lipid accumulation, inflammation and the intestinal barrier in MCD-fed mice were evaluated by detecting blood lipid levels, lipid accumulation, liver pathological changes, inflammatory factors, inflammatory signaling pathways, the three main short-chain fatty acids (acetate, propionate and butyrate), intestinal permeability and intestinal tight junction protein expression. Compared with the MCD-only group, baicalein intake decreased the serum and liver lipid levels. Moreover, the accumulation of lipid droplets and steatosis in the liver were also alleviated; all these results demonstrated that baicalein could alleviate NAFLD. Meanwhile, the levels of inflammatory cytokines decreased in the baicalein group. Further investigation of the mucosal permeability to 4 kDa fluorescein isothiocyanate–dextran, concentrations of short-chain fatty acids in feces, and the expression of intestinal zonula occluden 1 and claudin-1 indicated that a baicalein diet could decrease the intestinal permeability caused by a MCD diet. Moreover, the protein levels of p-NF-κB p65 and the ratio of p-NF-κB p65/NF-κB p65 increased, and IκB-α and PPARα decreased in NAFLD mice, while the administration of baicalein could alleviate these changes. The above results indicated that the mechanism of baicalein in the alleviation of NAFLD lies in the regulation of the intestinal barrier.